KNOWLEDGE MANAGEMENT DALAM KERANGKA PENGEMBANGAN KOMPETENSI STAF SUMBER DAYA MANUSIA KEPOLISIAN NEGARA REPUBLIK INDONESIA - Muhdiyati, Sarifah; Rajab, Ridwan; Saksono, R. N. Afsdy (Jurnal Academia Praja, 2024)
This research aims to examine the application of knowledge management in developing the competence of human resources staff within the Indonesian National Police (Polri). It analyzes relevant factors, including human resources, leadership, and organizational technology, through the lens of supporting conditions. The research employs a case study methodology, utilizing document analysis, interviews, and observation for data collection. The findings reveal that the implementation of knowledge management is not yet optimal. Regarding the human factor, it was discovered that the motivation to share knowledge is low due to the absence of incentives. In terms of leadership, the lack of commitment from leaders is evident in the absence of clear regulations. Concerning technology, various applications have been developed, but there is a lack of content or knowledge that supports daily work capabilities, such as standard operating procedures (SOPs). This research proposes a model for implementing knowledge management within the framework of competence development. This model comprises competence development planning with database strengthening (externalization), competence development implementation through knowledge transfer (socialization and internalization), and competence development evaluation by enriching modules and content (combination).